Analysis of the Effect of Occupational Safety and Health (OSH) Culture on Implementing OSH Awareness: A Case Study - Indah Pratiwi; Yusakh Ivanovic (Jurnal Teknik Industri, 2022)
Occupational Safety and Health (OSH) culture among students has not become a full awareness that is applied in everyday life in college. This study aims to identify, test, and analyze how much OSH culture influences implementing OSH awareness for students. The research was conducted on Industrial Engineering students at Universitas Muhammadiyah Surakarta (IE UMS) as many as 120 respondents from the class of 2016 to 2019 filled out a questionnaire about OSH culture. The method used in this study is the analysis approach of Structural Equation Modeling (SEM) variance-based or so-called Partial Least Square (PLS-SEM).   The variables in the OSH culture are four independent variables, namely: individual, organizational, occupational, and environmental with 18 sub-variables. Meanwhile, one dependent variable, awareness, consists of six sub-dependent variables. It was found that environmental, organizational, and occupational factors on awareness level significantly affect implementing OSH culture, and individual factors have no significant effect on the awareness level of implementing OSH culture. Thus, an improvement strategy is obtained by increasing environmental, organizational, and occupational preferences to maximize the implementation of OSH culture.